إظهار مميزات اللغة العربية عبر تنوع صيغ أوزنها واختلاف دلالاتها - السيوطى شعيب أولوغيلي (AR-RĀ’IQ, 2018)
Demonstrating the Arabic Language through the diversity of its scales and their different semantic. The main purpose of writing this paper is to demonstrate what Arabic Language contains in terms of semantic changes to structural changes of words scales in order for us to discover Arabic Language specification, such that differentiate it with others through our cognizance with those scales that imbue verbal structural building, which is being refer to as Arabic Language as “increase in structural building that benefits the increase in meaning”, such that makes Arabic Language the only one that enjoys this phenomenon, all this, is to highlight the advantages of conventional difference that make the Arabic Language leading to all other languages of the world.